2019
DOI: 10.3390/nu12010052
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Food Cravings and Eating Behavior after a Dietary Carbohydrate Restriction Intervention Trial

Abstract: Compared to low-fat diets, low-carbohydrate (CHO) diets cause weight loss (WL) over a faster time frame; however, it is unknown how changes in food cravings and eating behavior contribute to this more rapid WL in the early phases of dieting. We hypothesized that reductions in food cravings and improved eating behaviors would be evident even after a relatively short (4-week) duration of CHO-restriction, and that these changes would be associated with WL. Adult participants (n = 19, 53% males, mean ± SD: BMI = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…(3) Regarding the appearance of an intense desire for food resulting from this type of restriction, Castro et al, demonstrated a very low-calorie ketogenic diet (supervised prescription) did not cause increased food craving. (4) The same was described by Anguah et al, who verified a decrease of food craving and an increase by 102% in cognitive restraint, (5) when using a ketogenic diet with proportions of 14% of carbohydrates, 58% of fat and 28% of protein. In another randomized clinical trial using a low-carb diet, individuals who lost more weight had an increased desire for caloric foods in the sixth month, but gave in to desires less frequently.…”
Section: ❚ Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…(3) Regarding the appearance of an intense desire for food resulting from this type of restriction, Castro et al, demonstrated a very low-calorie ketogenic diet (supervised prescription) did not cause increased food craving. (4) The same was described by Anguah et al, who verified a decrease of food craving and an increase by 102% in cognitive restraint, (5) when using a ketogenic diet with proportions of 14% of carbohydrates, 58% of fat and 28% of protein. In another randomized clinical trial using a low-carb diet, individuals who lost more weight had an increased desire for caloric foods in the sixth month, but gave in to desires less frequently.…”
Section: ❚ Introductionsupporting
confidence: 59%
“…(21) Thus, carbohydrate restriction should be discussed as a possibility of intervention if it occurs under specialized care, for a determined time, with adaptation phases and behavioral evaluations. (4,5) Nevertheless, the prevalence of unsupervised practice of restrictive diets is increasing. (22)(23)(24)(25) Hume et al, demonstrated that individuals who went on successful diets reported lower consumption of carbohydrates, higher dietary restriction, higher protein intake, and more vigorous physical activity.…”
Section: Cognitive Restraint and Relation With Unsupervised Dietmentioning
confidence: 99%
See 2 more Smart Citations
“…It is undetermined if there is a specific diet that works best to limit flavor cravings. Low-carbohydrate diets have been associated with both reduced ( 130 , 138 , 139 ) and increased ( 131 ) sweet cravings compared with habitual diets. A role of genetics is uncertain.…”
Section: Extremes Of Hedonicsmentioning
confidence: 99%